Analysis of the impact of the financial crisis on providing basic needs for the residents of Sulaymaniyah city in 2016 - Ahmed Hussein Batal; Sardar Osman Khader Badaway; Kamran Ahmed Hama (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
reflected negatively on all economic sectors, including the household sector, especially in the province of Sulaymaniyah, and that the continuation of this crisis will lead to a paralysis of most economic sectors in the province, and then lead to increased poverty rate in the province, especially among owners with limited income. And research has reached a number of conclusions, including: The proportion (65.2%) of the households surveyed monthly income between (300-900) thousand dinars. The proportion (60.6%) of the households surveyed monthly spending between (1-600) thousand dinars. The results show there is a difference between the averages of the questionnaire answers depending on the size of the spending in the impact of financial crisis on basic needs. 3- The study found that the percentage (50%) of the households surveyed in the city of Sulaimaniya their savings monthly negative, and a special category of entry (less than 300) thousand dinars per month. 4-The provision of drinking water and safety services as well as home hygiene, which means not affected by these services by the financial crisis, while there we find the effect of the crisis on all other services, including basic services such as food, clothing, housing and the availability of electric power, communication expenses and the net and fuel. The research found a number of proposals including; 1-Create a permanent economic commission, far from partisan considerations, experts and specialists develop scenarios to address the current crisis and the expected in the region. 2-activate price control in the consumer markets and protect consumers in the region.